Halal Entrepreneurship by Using the Global Gotong-Royong (G2R) Tetrapreneur Approach: a Bibliometric Review and Research Framework - Rozaq Muhammad Yasin; P.L. Rika Fatimah; Diana Shofa (International Journal of Islamic Business and Economics (IJIBEC), 2025)
This study aims to examine publication patterns on halal entrepreneurship by using the global gotong-royong (G2R) tetrapreneur approach. This study conducted a quantitative bibliometric analysis using the Scopus database from 2004 to 2025. The search terms "Entrepreneurship" and "Halal entrepreneurship", combined with "Islamic entrepreneurship", "halalpreneurship", "halalpreneurial", "halal success story", "halal digital entrepreneurship", "Halalan-Toyyiban" yielded 89 articles. The data were processed in RStudio using the Bibliometrix R package, specifically the Biblioshiny component. The results of the bibliometric analysis indicate a significant increase in research interest in halal entrepreneurship from 2010 to 2025. This analysis also explains the relationships among the most productive authors based on the country of their university affiliation, collaborations, the most cited documents, keywords, and the scientific knowledge used. A comprehensive literature review will be invaluable to future researchers seeking to build a strong conceptual framework. Scientific mapping in this study is imited to the Scopus database and programming languages. To the author's knowledge, this study is the first to describe a research pattern that focuses on halal entrepreneurship by using the Global Gotong-Royong (G2R) Tetrapreneur approach to illustrate future research